The influence of Voluntary Disclosure, Asymmetri Information, Stock Risk, Firm Size and Institutional Ownership Towards Cost of Capital (COC) - Fahdiansyah, Restu (Jurnal Aplikasi Manajemen, 2016)
Abstract: This study aims to determine the influence of the information toward the decisions taken by investors based on the theory of Efficient Markets Hypothesis (EMH), which is expressed by Fama (1970),by examining the influence of several independent variables towards the cost of capital (COC). Independent variables were used to reflect information, including voluntary disclosure, information asymmetry, risk stock, firm size and institutional ownership. This study used purposive sampling technique in conducting sample of the 131 manufacturing companies listed on the Indonesia Stock Exchange in 2011, which produced 75 research samples. This study used the linear regression to analyze the data. The results of this study indicate that there is an influence of the informationtoward the decision making of investors, which is seen from the simultaneous test results that show all variables simultaneously influencing the COC. The results also indicate that voluntary disclosure variables, the risk of the stock, and the firm size are partially influencing the COC, whereas the information asymmetry variables and institutional ownership are partially show no influence on the COC.